DIAGNOSIS OF BRAIN AND NERVE INJURIES, A COMPREHENSIVE STUDY - Jobran Saeed Harisi, Abdulrahman Mohammad Hussein Alabdullah, Wesam Saad Saleh Alotaibi, Mohammed Saeed Bin Shahir,; Mohammed Ali Hommadi, Abdullah Mubarak Saad Mesfer, Ahmed Budary Ghazi Alotaibi, (Chelonian Research Foundation, 2024)
Brain and nerve injuries are complex medical conditions that require accurate and timely diagnosis for appropriate treatment and management. This essay explores various methods used in the diagnosis of brain and nerve injuries. The key diagnostic tools discussed include imaging techniques such as CT scans, MRI, and PET scans, as well as neurological tests like EMG and EEG. The essay also highlights the significance of a comprehensive patient history and physical examination in the diagnostic process. Additionally, the role of new technologies such as artificial intelligence in improving diagnostic accuracy is also examined. Overall, an integrative approach combining clinical assessment with advanced diagnostic tools is essential for effective management of brain and nerve injuries. Keywords: brain injuries, nerve injuries, diagnosis, imaging techniques, neurological tests, artificial intelligence